Joshua Tree - Shepherd, Jodie (2019)
Readers will hike through the entire park to get a glimpse of its fascinating rock formations and amazing plants and animals. They will also learn about the park's history, how people are working to preserve its natural beauty today, and more.
Includes bibliographical references and index.
7-10
Keywords: Joshua Tree National Park (Calif.) -- Juvenile literature